Biomarkers in community-acquired pneumonia: still searching for the one. Issue 2 (28th February 2019) - Sibila, Oriol; Restrepo, Marcos I.
Community-acquired pneumonia (CAP) remains a major cause of morbidity and mortality worldwide [1]. Despite advances in antibiotic treatment and medical care, the mortality of CAP is still high in hospitalised patients, especially in those with severe illness [2]. Appropriate initial severity assessment is a crucial step in pneumonia management, since it has been demonstrated that an early recognition of severe CAP patients improves their clinical outcomes [3]. Several tools have been developed to evaluate disease severity, in particular focusing on predicting hospital admission and mortality [4]. However, recent studies have showed that most of these scores are not used routinely in clinical practice and may be inadequate tools to guide appropriate antibiotic treatment [5, 6]. Fibroblast growth factor 21 (FGF21) predicts severity of illness, clinical stability and mortality in community-acquired pneumonia. Validation is needed to confirm the application of FGF21 in clinical practice. http://ow.ly/SYI730nuRc1